The Calculus Behind Generic Drug Equivalence. (1st January 2018) - Huddy, Stanley R.; Jones, Michael A.
Summary: To show bioequivalence of generic and brand name drugs, the Food and Drug Administration (FDA) requires a statistical comparison of three pharmacokinetic values that measure aspects of the drugs' concentrations. These three values are related to calculus. We show that there is good reason why the FDA considers these values, as any two of the three is enough to recover the concentration of the drug over time for an orally taken drug using a single-compartment model. The results hinge on applications of the Lambert W function.